2012
DOI: 10.3747/co.19.1069
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Multidisciplinary Team Management of Patients with Non-Small-Cell Lung Cancer

Abstract: Historically, a simple approach to the treatment of non-small-cell lung cancer (nsclc) was applicable to nearly all patients. Recently, a more complex treatment algorithm has emerged, driven by both pathologic and molecular phenotype. This increasing complexity underscores the importance of a multidisciplinary team approach to the diagnosis, treatment, and supportive care of patients with nsclc. A team approach to management is important at all points: from diagnosis, through treatment, to end-of-life care. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 60 publications
0
45
0
2
Order By: Relevance
“…Multidisciplinary care planning in early stage NSCLC likely reduces delays in treatment and improves adherence to treatment guidelines. 10 However the use of an interdisciplinary approach to focus on the survivorā€™s physical, emotional, and spiritual well-being during post-operative recovery has not been reported. An interdisciplinary team approach integrates various disciplines into holistic survivor-centered encounters.…”
mentioning
confidence: 99%
“…Multidisciplinary care planning in early stage NSCLC likely reduces delays in treatment and improves adherence to treatment guidelines. 10 However the use of an interdisciplinary approach to focus on the survivorā€™s physical, emotional, and spiritual well-being during post-operative recovery has not been reported. An interdisciplinary team approach integrates various disciplines into holistic survivor-centered encounters.…”
mentioning
confidence: 99%
“…It is believed that lung cancer care in general as well as palliative care can be provided more successfully by a multidisciplinary team [25,26]. The wide variety of problems that have been outlined in this article shows the need to be organised in a multiprofession manner, and research seems to confirm this recommended approach.…”
Section: Organisation Of Palliative Carementioning
confidence: 85%
“…For the management of DFEA patients, a multidisciplinary approach is also necessary to improve PS and facilitate patient-centred decision making for most patients. Furthermore, previous studies also demonstrated that this approach had many benefits for patients with advanced lung cancer [27][28][29][30]. Therefore, a multidisciplinary approach should be employed for the treatment of advanced lung cancer patients, especially for DFEA patients.…”
Section: Discussionmentioning
confidence: 99%